European eel ( Anguilla anguilla ) survival modeling based on a 22‐year capture‐mark‐recapture survey of a Mediterranean subpopulation - Amélie Hoste; Colin Bouchard; Jean‐Christophe Poggiale; Delphine Nicolas (Journal of Fish Biology, 2025)
Since the 1980s, the European eel ( Anguilla anguilla ) has declined by over 90% in recruitment across its European and North African distribution area. This diadromous fish spawns at sea and migrates into continental waters, where it grows for three to more than 30 years, depending on habitat conditions and location. During their growth, different habitat use tactics can locally influence the life‐history traits of eels, including their survival rates. Thus, the spatio‐temporal dimension of this species is crucial for management. Based on a rare Mediterranean long‐term survey of more than 20 years (2001–2022) in an artificial drainage canal connected to a vast brackish lagoon (the Vaccarès lagoon), we aimed to study the dynamics of one subpopulation's life‐history traits. We used Bayesian multistate capture‐mark‐recapture (CMR) models to assess the temporal variability in survival and abundance at both seasonal and inter‐annual scales, considering life‐stage structure. High survival rates and low detection probabilities were found for the undifferentiated and female yellow stages. In contrast, female silver eels exhibited lower survival rates and higher capture probabilities. Estimating detection probabilities and survival rates enabled accurate assessment of relative abundance across different life stages and time periods. Our findings indicated a substantial decrease in the abundance of undifferentiated and female yellow eels in the early 2000s, whereas the abundance of female silver eels remained consistently low yet stable throughout the study period. Considering the life stage seemed essential to study the dynamics of the eel during its continental growing period. The present results will provide key elements to propose and implement suitable sustainable environmental management strategies for eel conservation.

Investigating the quality of European silver eels by quantifying contaminants and parasite infestation in a French Mediterranean lagoon complex - Amélie Hoste; Raphaël Lagarde; Elsa Amilhat; Colin Bouchard; Paco Bustamante; Adrian Covaci; Elisabeth Faliex; Emmanuelle Migne; Giulia Poma; Claire Tetrel; Klervi Verbrugghe; Hugo Vey Payre; et al. (Environmental Science and Pollution Research, 2025)

Unravelling the metabolomic signatures of migrant and non-migrant glass eels (Anguilla anguilla) and their response to diazepam exposure - Iker Alvarez-Mora; Valérie Bolliet; Naroa Lopez-Herguedas; Colin Bouchard; Mathilde Monperrus; Nestor Etxebarria (Marine Environmental Research, 2024)

Influence of changes in local environmental variables on the distribution and abundance dynamics of wintering Teal Anas crecca - David Vallecillo; Matthieu Guillemain; Colin Bouchard; Sébastien Roques; Jocelyn Champagnon (Biodiversity and Conservation, 2023)

Considering temporal variations in mating opportunities: consequences for sexual selection estimates - Léa Daupagne; Colin Bouchard; Anne Michaud; Marius Dhamelincourt; Emilien Lasne; Cédric Tentelier (Animal Behaviour, 2023)

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Sexual maturity increases mobility and heterogeneity in individual space use in Atlantic salmon ( Salmo salar ) parr - Colin Bouchard; Frédéric Lange; François Guéraud; Jacques Rives; Cédric Tentelier (Journal of Fish Biology, 2020)
We assessed the effects of sexual maturity on space use in Atlantic salmon ( Salmo salar ) parr as facultative early maturation enables us to work on individuals belonging to the same cohort. We monitored the space use of 40 1‐year‐old males in natura throughout a breeding season. First, mature individuals covered longer distances (absolute and upstream) and located within broader home ranges than immature parr. Second, sexual maturity also generated a higher interindividual variability in space use. Finally, mature individuals exhibited a higher probability of association with likely breeding sites on average. However, some mature individuals experienced a lower probability than immature individuals, suggesting that the space use of some mature individuals may not be optimal. Moreover, mature parr exploiting a broader home range or covering longer upstream distances had a higher probability of association with likely breeding sites. Covering longer upstream distances may therefore increase the reproductive success of mature parr, while involving higher energetic costs and a greater risk of predation.